Bovine serum albumin-modified 3D printed alginate dialdehyde-gelatin scaffolds incorporating polydopamine/SiO2-CaO nanoparticles for bone regeneration - Kim, Myong-Ho; Schöbel, Lisa; Geske, Michael; Boccaccini, Aldo R.; Ghorbani, Farnaz (International Journal of Biological Macromolecules, 2024)
Three-dimensional (3D) printing allows precise manufacturing of bone scaffolds for patient-specific applications and is one of the most recently developed and implemented technologies. In this study, bilayer and multimaterial alginate dialdehyde-gelatin (ADA-GEL) scaffolds incorporating polydopamine (PDA)/SiO2-CaO nanoparticle complexes were 3D printed using a pneumatic extrusion-based 3D printing technology and further modified on the surface with bovine serum albumin (BSA) for application in bone regeneration. The morphology, chemistry, and in vitro bioactivity of PDA/SiO2-CaO nanoparticle complexes were characterized (n = 3) and compared with those of mesoporous SiO2-CaO nanoparticles. Successful deposition of the PDA layer on the surface of the SiO2-CaO nanoparticles allowed better dispersion in a liquid medium and showed enhanced bioactivity. Rheological studies (n = 3) of ADA-GEL inks consisting of PDA/SiO2-CaO nanoparticle complexes showed results that may indicate better injectability and printability behavior compared to ADA-GEL inks incorporating unmodified nanoparticles. Microscopic observations of 3D printed scaffolds revealed that PDA/SiO2-CaO nanoparticle complexes introduced additional topography onto the surface of 3D printed scaffolds. Additionally, the modified scaffolds were mechanically stable and elastic, closely mimicking the properties of natural bone. Furthermore, protein-coated bilayer scaffolds displayed controllable absorption and biodegradation, enhanced bioactivity, MC3T3-E1 cell adhesion, proliferation, and higher alkaline phosphatase (ALP) activity (n = 3) compared to unmodified scaffolds. Consequently, the present results confirm that ADA-GEL scaffolds incorporating PDA/SiO2-CaO nanoparticle complexes modified with BSA offer a promising approach for bone regeneration applications.
CRIS-Team Scopus Importer:2024-03-22
Keywords: 3D printing; Alginate dialdehyde-gelatin; Bovine serum albumin; Polydopamine; Silica-calcia; Tissue engineering